A legal study on medical apology / Mohd Rizlan Shah Izman and Rahmat Mohamed Hazlan - Izman, Mohd Rizlan Shah; Mohamed Hazlan, Rahmat (2012)
The reputation of the medical profession has been questioned on numerous occasions. Despite being highly respected by the society, refusal of doctors to apologize whenever there occurs an adverse event has caused a serious dent to their status as lifesavers. This leads to the argument of whether we should have a law to protect a doctor's statement of apology by making it inadmissible to establish liability in court. This research will highlight the underlying principles behind an apology law and the need of having the law to protect a statement of apology by doctors. We will look into cases in other countries and how liability can be established based on disclosure and apology. Furthermore, the research will study various statutes from Canada, United Kingdom and the United States of America that govern a statement of apology. Data and information of this research were gathered from books, journals, online articles and interviews with academicians. It is hoped that this research will fulfill the objectives and will be a guideline in determining whether there should be a law to protect medical apologies in Malaysia.